Hermeneutyka i ἄσκησις. O żywotności Platońskiej μελέτης θανάτου - Wandowicz, Mieszko (Przestrzenie Teorii, 2019)
Philosophy is, first and foremost, the art of self-discovery. It has been that since its dawn, from the Delphic oracle to the present day. This is why pieces of ancient writing should be read as stimuli to one’s own thinking, so as to (in the name of hermeneutic fairness) not offend the old masters. A fragment which serves this purpose better and better as uncertainty of the author’s intentions grows is “μελέτη θανάτου” (Plato, Phaedo). The variety of possible translations enables this: “practice of death”, “care for death”, “exercise in death”, along with a range of thanatological questions, all but independent from the translations themselves. The abundance of possible interpretations also helps remind us of something which is well worth remembering: words are more of a tool aiding understanding than the actual aim of that understanding.